2020
DOI: 10.1016/j.heliyon.2020.e04309
|View full text |Cite
|
Sign up to set email alerts
|

Unintended pregnancy and associated factors among unmarried female students: A case of Bahir Dar University

Abstract: Background: Unintended pregnancy is a mistimed, unplanned or unwanted pregnancy at the time of conception. Unintended pregnancy has a number of adverse physical, mental, and social impacts. It brings illegal and unsafe abortions which are causes of maternal morbidity and mortality in the developing countries like Ethiopia. Even if such problem has significant impact on the community, there is scarcity of evidence on this issue in Ethiopian higher institutions. Therefore, this study was aimed to assess unintend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Our study used a SEM to explore how household head age contributed to the persistent adolescent pregnancy in Nigeria, particularly during the study period between 2013 and 2018. This study demonstrates that the independent variables of interest (household head age at the SEM interpersonal level) examined for this study was associated with higher risk of adolescent pregnancy (intrapersonal level characteristics) in Nigeria aged 15–19 years during the study period; illustrating that this factor should be targeted with SEM-based preventive programs that allow intervention planners to take into account how community, organizational, and policy levels could also contribute to or diminish success of interventions [ 27 ]. Furthermore, the entry point for the intervention relative to household head age is evident at age group with higher prevalence of adolescent pregnancy: younger household heads (15–24 (58.5%) and 25–34 (62.9%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study used a SEM to explore how household head age contributed to the persistent adolescent pregnancy in Nigeria, particularly during the study period between 2013 and 2018. This study demonstrates that the independent variables of interest (household head age at the SEM interpersonal level) examined for this study was associated with higher risk of adolescent pregnancy (intrapersonal level characteristics) in Nigeria aged 15–19 years during the study period; illustrating that this factor should be targeted with SEM-based preventive programs that allow intervention planners to take into account how community, organizational, and policy levels could also contribute to or diminish success of interventions [ 27 ]. Furthermore, the entry point for the intervention relative to household head age is evident at age group with higher prevalence of adolescent pregnancy: younger household heads (15–24 (58.5%) and 25–34 (62.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Other factors at the interpersonal level are parents, household heads, family wealth, schools, teachers, peers, health care providers, friends, health literacy, marital status, household size, parenting style, beliefs, attitudes, and family norms. In contrast, policies enacted at the policy level of the SEM must interact or filter through three levels (organizational, community, and interpersonal) before reaching the intrapersonal level, therefore, planners must be attentive to policy alignment for any intervention to be effective, especially at the rural environment [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Gite [22] in Ethiopia, Belay. [23] In North West Ethiopia and Aly Nor [14]., Amasha, Salah Salama [24] in Port-said, Egypt found that the age at the first marriage less than or equal to 18 years were six times more likely to experience UP than their counter parts. Unlikely, Abdel-Haleem [25] revealed that women with unintended pregnancy were married at the age more than 20 compared to those who had intended pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…16 Similarly, another study conducted revealed that having multiple sexual partners, non-use of condom and nonconsensual sex and sexual intercourse before high school potentiated unintended pregnancy. 17 The drivers of unintended pregnancies in sub-Saharan Africa are complex and operate at individual, household, community and policy levels. Understanding them is important to develop policies and effective interventions to reduce unintended pregnancies and unsafe abortion in the region.…”
Section: Introductionmentioning
confidence: 99%